Synergistic mechanism of olaparib and cisplatin on breast cancer elucidated by network pharmacology - Qiang Niu; Tao Zhang (Scientific Reports)
Abstract Cisplatin is an important chemotherapeutic agent is widely used to treat breast cancer and olaparib is the most studied PARP inhibitor to date. To explore the combinational anti-cancer potential and synergistic mechanism of Olaparib and cisplatin in breast cancer using network pharmacology. Drugs targets were drawn from PharmMapper, DrugBank, BATMAN-TCM, DrugCentral, STITCH, Swiss Institude of Bioinformatics and Comparative Toxigenomics Database (CTD). Breast cancer targets were extracted from OMIM, KEGG, GeneCards and DrugBank. The protein-protein interaction (PPI) network was created using the STRING database. Core targets were selected by incorporating PPI networks using Cytoscape 3.9.1. GO and KEGG analyses were performed to investigate common targets of Olaparib and cisplatin in breast cancer. The drug-disease-target network contained 82 nodes and 901 edges. The common targets obtained from Olaparib, cisplatin and breast cancer were identified, including ATK, p53, caspase-3, HSP90AA1, IL-6, IL-1β, ANXA5, SIRT1, caspase-9 and PARP. Core targets were primarily related to response to reactive oxygen species, regulation of apoptotic signaling pathway, regulation of DNA metabolic process, and regulation of cell activation. The KEGG pathway analysis revealed that Olaparib and cisplatin may affect breast cancer through platinum drug resistance and longevity regulating pathway. Furthermore, Olaparib combined with cisplatin downregulated the expression of caspase-3 and caspase-9 proteins and upregulated p53, PARP, and SIRT1 protein levels in MCF-7 cells. Functionally, the cooperative effect of Olaparib and cisplatin reduced the applied concentration of cisplatin and enhanced the anticancer effect, emphasizing the importance of combination therapy to overcome side effects and significantly improve the anticancer efficacy of cisplatin.